The Black Sea region and EU policy the challenge of divergent agendas - Henderson, Karen; Weaver, Carol (Ashgate Pub., 2010)
Designed to further the debate on the future of EU policies for the Black Sea region, this book is an essential resource for students and researchers in search for a coherent picture of the inter-relationship of EU initiatives and policies in the region.